Conservative management in very elderly patients with severe aortic stenosis: Time to change?. Issue 6 (June 2017) - Bernal, Eva; Ariza-Solé, Albert; Formiga, Francesc; Abu-Assi, Emad; Carol, Antoni; Galián, Laura; Bayés-Genís, Antoni; Saldivar, Hugo González; Díez-Villanueva, Pablo; Sellés, Manuel Martínez; ,
Abstract: Background: Despite current recommendations, a high percentage of patients with severe symptomatic aortic stenosis are managed conservatively. The aim of this study was to study symptomatic patients undergoing conservative management from the IDEAS registry, describing their baseline clinical characteristics, mortality, and the causes according to the reason for conservative management. Methods: Consecutive patients with severe aortic stenosis diagnosed at 48 centers during January 2014 were included. Baseline clinical characteristics, echocardiographic data, Charlson index, and EuroSCORE-II were registered, including vital status and performance of valve intervention during one-year follow-up. For the purpose of this substudy we assessed symptomatic patients undergoing conservative management, including them in 5 groups according to the reason for performing conservative management [I: comorbidity/frailty (128, 43.8%); II: dementia 18 (6.2%); III: advanced age 34 (11.6%); IV: patients' refusal 62 (21.2%); and V: other reasons 50 (17.1%)]. Results: We included 292 patients aged 81.5 ± 9 years. Patients from group I had higher Charlson index (4 ± 2.3), higher EuroSCORE-II (7.5 ± 6), and a higher overall (42.2%) and non-cardiac mortality (16.4%) than the other groups. In contrast, patients from group III had fewer comorbidities, lower EuroSCORE-II (4 ± 2.5), and low overall (20.6%) and non-cardiac mortality (5.9%). Conclusions: Patients with severe symptomatic aortic stenosis managed conservatively have different baseline characteristics and clinical course according to the reason for performing conservative management. A prospective assessment of comorbidity and other geriatric syndromes might contribute to improve therapeutic strategy in this clinical setting.